2008
DOI: 10.1111/j.1468-2354.2008.00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration Level, Probability of Success and Failure, and Expected Utility*

Abstract: Aspiration levels are a relevant aspect of decision making. We develop a model that includes the overall probabilities of success and failure relative to the aspiration level into an expected utility representation. This turns out to be equivalent to expected utility with a discontinuous utility function. We give a behavioral foundation to the proposed model and provide conditions to determine the relative weights of the overall probabilities of success and failure. An aspiration level reinforces loss aversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(72 citation statements)
references
References 58 publications
2
60
0
1
Order By: Relevance
“…We structured the choice environments to make the trade-off between number and magnitude of positive outcomes negligible ($0.08 in the first choice environment, referred to as Game A) or much more significant ($1.25 in the second choice environment, referred to as Game B). Diecidue and van de Ven (2008) viewed this trade-off of EV maximization and P(win) maximization within a more general expected utility framework, implying that the larger the EV difference, the more choices should shift toward the HiEVoption and away from the P(win) option. Note that the negligible EV difference in Game A allowed us to simultaneously preserve the rank ordering of gambles across game environments and maintain the reasonableness of Dijksterhuis and his colleagues' operationalization of accurate choice as the P(win) option in the Game A environment.…”
Section: Replicating Dijksterhuis's Environment: P(win)mentioning
confidence: 98%
“…We structured the choice environments to make the trade-off between number and magnitude of positive outcomes negligible ($0.08 in the first choice environment, referred to as Game A) or much more significant ($1.25 in the second choice environment, referred to as Game B). Diecidue and van de Ven (2008) viewed this trade-off of EV maximization and P(win) maximization within a more general expected utility framework, implying that the larger the EV difference, the more choices should shift toward the HiEVoption and away from the P(win) option. Note that the negligible EV difference in Game A allowed us to simultaneously preserve the rank ordering of gambles across game environments and maintain the reasonableness of Dijksterhuis and his colleagues' operationalization of accurate choice as the P(win) option in the Game A environment.…”
Section: Replicating Dijksterhuis's Environment: P(win)mentioning
confidence: 98%
“…A number of studies have in fact suggested that it is not the case to be completely insensitive to such magnitude variations, particularly with respect to losses (Payne, Laughhunn, & Crum, 1980). More recently, it has been argued that a model which solely maximizes the success probability is too crude to be normatively or descriptively relevant (Diecidue & Van de Ven, 2008).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…At the beginning of a cycle, each farmer adjusts their economic aspirations according to the expected status of relevant contextual factors (i.e., climate conditions, output prices, and input costs). This initial adjustment is part of each farmer's dynamic update of their aspiration level (AL) (Diecidue and van de Ven, 2008). Then, the farmer updates the area they will crop, deciding whether to exit, return or stay in production and, in the last case, reducing, maintaining or expanding the previous area.…”
Section: The Pampas Modelmentioning
confidence: 99%